Wave nature of conduction electrons in amorphous Co90Sc10 and Fe90Sc10 alloys. (18th October 2018) - Ghafari, M; Louzguine-Luzgin, D V; Hutchison, W D; Feng, T; Campbell, S J
Abstract: The resistivity of amorphous Fe90 Sc10 and Co90 Sc10 alloys can be described well in terms of a simple model based on the wave character of electrons and their associated tunnelling over the temperature ranges 1.9 K to 135 K and 1.9 K to 12 K respectively. The extended range of agreement between experiment and theory for amorphous Fe90 Sc10 is linked with its relatively small mean free path of = 0.32 nm, thus allowing electron waves to tunnel between clusters. On the other hand the restricted region of tunnelling of electron waves for amorphous Co90 Sc10 alloys is linked with its relatively large mean free path of = 0.48 nm which restricts the ability for tunnelling between clusters while enabling electron waves to tunnel between different regions with a cluster.